Doskonalenie procesu obsługi klienta w systemie zarządzania jakością - Mazur, Anna; Gołaś, Hanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents differences between quality of a product and a service. Requirements of quality management system connected with customer service are given. The example of customer service process and its improvement according with PN-EN ISO 9001:2001 standard is presented. Authors present differences in approach to customer requirements identification and methods and tools used in production and service companies. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 33-39